Effects of Hydrogen-Rich Water on Interleukin-1β, Number of Osteoclasts and Osteoblasts in Streptozotocin-induced Diabetic Rats with Orthodontic Tooth Movement - Lina Hadi; Albert Manggading Hutapea; Florenly Florenly (The Prodia Education and Research Institute (PERI), 2023)
BACKGROUND: Orthodontic tooth movement (OTM) may increase the risk of treatment-related complications for some diabetes mellitus (DM) patients. Hydrogen-rich water (HRW) has been demonstrated in many studies to reduce oxidative stress and cell damage. This study aimed to examine the levels of interleukin (IL)-1β, blood glucose level, body weight, tooth displacement, and population of osteoclasts and osteoblasts in diabetic rats with OTM.METHODS: Thirty rats (Rattus novergicus) were divided into 6 groups: OTM, HRW, DM, DM+OTM, DM+HRW, and DM+OTM+HRW. DM, DM+OTM, DM+HRW, and DM+OTM+HRW groups were induced with streptozotocin (STZ) after 8 weeks of high-fat diet (HFD) and continued being fed HFD for 4 weeks. OTM, DM+OTM, and DM+OTM+HRW groups were placed on an orthodontic device for the orthodontic treatment. HRW, DM+HRW, and DM+OTM+HRW groups were administered HRW via oral gavage 3 times a day for 4 weeks. At the end of the study, all rats were euthanized and blood samples were collected for IL-1β measurement using enzyme-linked immunosorbent assay (ELISA) kits. Meanwhile, the rats’ maxilla was taken to measure tooth movement, and the number of osteoclast and osteoblast were counted.RESULTS: The highest increase of IL-1β was in the DM+OTM group (140.07±5.14 pg/mL) and the lowest was in the HRW group (92.80±2.89 pg/mL). The average number of osteoblasts were higher in tension sites, while osteoclasts were higher in pressure sites.CONCLUSION: Consumption of HRW in STZ-induced diabetic rats with OTM can reduce IL-1β levels, reduce tooth mobility, and promote bone remodeling.KEYWORDS: diabetes mellitus, hydrogen rich water, interleukin-1β, orthodontic tooth movement, osteoblast, osteoclast